University students’ awareness and use of ecolabels: A case of the university of education, Winneba - Henaku, Eugene Adu; Amu, Theresa Alexandra (American Journal of Education and Learning, 2023)
Ecolabels are used to create environmental awareness and to direct individuals toward sustainable consumption. This study explored the awareness and use of ecolabels in purchasing decisions among students at the University of Education, Winneba, Ghana. The exploratory survey design was employed in this study. An online survey which had 18 items, was used to collect data from two hundred and sixty-six (266) students. The data collected were processed via SPSS version 25.0 and analysed using frequency and percentage. The results were presented in tables, followed by their interpretation and discussion. Generally, students’ awareness of ecolabels is below average. Most students (n=131; 49%) are unaware of ecolabels such as Ghana Green Label, Fairtrade and Voltic Ghana Eco-logo. In addition, the study found that the majority of students do not notice and search for ecolabels while shopping. Further, the study found that students who purchased products with ecolabels were below average. However, the majority of students (72.93%) trust that products carrying ecolabels are environmentally friendly and are willing to pay more for products bearing ecolabels. Therefore, the study recommended that producers, organisations and institutions such as the Environmental Protection Agency-Ghana (EPA-Ghana) should increase the awareness of ecolabels and the need to use ecolabels in purchasing decisions.